2013
DOI: 10.1159/000348515
|View full text |Cite
|
Sign up to set email alerts
|

Acute Encephalopathy with Unilateral Cortical-Subcortical Lesions in Two Unrelated Kindreds Treated with Glucocorticoids Prenatally for Congenital Adrenal Hyperplasia due to 21-Hydroxylase Deficiency: Established Facts and Novel Insight

Abstract: Background: Prenatal glucocorticoid (GC) treatment of the female fetus with 21-hydroxylase deficiency (21-OHD) may prevent genital virilization and androgen effects on the brain, but prenatal GC therapy is controversial because of possible adverse effects on fetal programming, the cardiovascular system and the brain. Case Reports: We report 2 patients with congenital adrenal hyperplasia (CAH) due to 21-OHD who were treated prenatally with dexamethasone, suffered from an acute encephalopathy and showed focal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Among pregnancies at risk for CAH, prenatally Dex-treated newborns have lower, but nominally normal, birth weights compared to untreated controls (470); the decrease averages ~400 g (471). Other adverse events including failure to thrive, stroke-like events and midline defects have been observed in both shortterm and full-term treated cases at risk for CAH (472)(473)(474).…”
Section: Fetal Safetymentioning
confidence: 99%
“…Among pregnancies at risk for CAH, prenatally Dex-treated newborns have lower, but nominally normal, birth weights compared to untreated controls (470); the decrease averages ~400 g (471). Other adverse events including failure to thrive, stroke-like events and midline defects have been observed in both shortterm and full-term treated cases at risk for CAH (472)(473)(474).…”
Section: Fetal Safetymentioning
confidence: 99%
“…In the literature, a few cases have been reported with acute encephalopathy or encephalopathic episodes in CAH patients [3,4,5]. Here, we report a case with CAH, presented with acute encephalopathy.…”
Section: Introductionmentioning
confidence: 81%
“…Intravenous hydrocortisone was administered but his level of consciousness did not recover. Recently, cases of CAH-related encephalopathy have been reported in literatüre [3,4,5]. Le et al [3] reported acute encephalopathy in three patients with CAH.…”
Section: Case Reportmentioning
confidence: 99%
“…Some authors have reported an increased risk for normal to low birth weight and for cerebral palsy, albeit non-statistically significant [ 67 ]. Grunt et al reported two cases of acute encephalopathy, one of which with permanent sequelae [ 68 ].…”
Section: Cah and Pregnancymentioning
confidence: 99%